Fostering Inclusive Growth in Indonesia: Evidence from Panel Regression Analysis - Della Hardyati Prabowo; Ghozali Maski; Dwi Budi Santoso (AIBPM Publisher, 2022)
An inclusive development does not only rely on economic growth but also on the creation of equitable access to growth outcomes. Government spending has an important role in promoting efficiency and economic growth as well as equity. Meanwhile, financial inclusion is believed to be able to expand opportunities to contribute to growth. Previous studies have proven the influence of both on inclusive growth with varying results. This study aims to analyze the impact of government spending in the fields of health, education, economy, and social protection, as well as financial inclusion on inclusive growth. Using panel data from 34 provinces in Indonesia in 2015-2019, this study applies a random effects model. The results show that education spending and the level of financial inclusion can foster inclusive growth. This finding confirms that public investment in education will expand access to education to increase human capital and labor productivity, as well as competitiveness and wages, while the inclusiveness of financial services increases access to more affordable credit. On the other hand, economic spending has a negative impact on inclusive growth due to the development gap. Meanwhile, health and social protection spending have no impact on inclusive growth. The implication is that health and economic spending policies must be directed at ensuring people's access to more equitable economic opportunities. Monitoring and provision of a more active social assistance also needs to be improved. Keywords: Financial Inclusion, Government Spending, Inclusive Growth, Panel Regression